The Concept of Anomie in Explaining Crime - Lau, Ting Fang Tiffany (Bellarmine Law Society Review, 2020)
The sociological concept of anomie, describing the breakdown of ethical standards, has been widely influential in the field of criminology. This article examines the explanatory power of classical and contemporary anomie theories (namely Strain Theory and Institutional Anomie Theory) in understanding a vast array of crimes as well as exploring the effects of dramatic sociocultural changes in modern history. The article concludes that anomie theories provide robust explanations for certain types of crime (specifically property crime, violent crime, organized crime, and white-collar crime) and notes the empirical challenges in assessing the validity of such theories.